Cyber Threat Intelligence: Enhancing Higher Education Security (The National University of Malaysia-Oct 2018) - Seyedmostafa Safavi (680970) (2025)
This presentation explores the evolving cybersecurity landscape in higher education and the critical role of Cyber Threat Intelligence (CTI) in mitigating risks. It outlines common cyber threats faced by universities, including phishing, ransomware, and insider threats, and discusses the implementation of intelligence-driven security strategies. The study emphasizes the importance of proactive threat monitoring, intelligence-sharing frameworks, and institutional collaboration to enhance cybersecurity resilience in academic environments.